The Agr Quorum Sensing System Represses Persister Formation through Regulation of Phenol Soluble Modulins in Staphylococcus aureus - Xu, Tao; Wang, Xu-Yang; Cui, Peng; Zhang, Yu-Meng; Zhang, Wen-Hong; Zhang, Ying (Frontiers in Microbiology, 2017)
The opportunistic pathogen Staphylococcus aureus has become an increasing threat to public health. Its pathogenicity is an expression of both virulence and persister formation.While the Agr quorum sensing (QS) system is a master regulator of S. aureus virulence, its dysfunction has been frequently reported to promote bacteremia and mortality in clinical infections. Here we show that the Agr system is involved in persister formation in S. aureus. Mutation of either agrCA or agrD but not RNAIII resulted in increased persister formation of stationary phase cultures. RNA-seq analysis showed that in stationary phase AgrCA/AgrD and RNAIII mutants showed consistent up-regulation of virulence associated genes (lip and splE, et al.) and down-regulation of metabolism genes (bioA and nanK, etc.). Meanwhile, though knockout of agrCA or agrD strongly repressed expression of phenol soluble modulin encoding genes psma1-4, psmb1-2 and PSM transporter encoding genes in the pmt operon, mutation of RNAIII enhanced expression of the genes. We further found that knockout of psma1-4 or psmb1-2 augmented persister formation and that co-overexpression of PSMas and PSMbs reversed the effects of AgrCA mutation on persister formation. We also detected the effects on persister formation by mutations of metabolism genes (arcA, hutU, narG, nanK, etc.) that are potentially regulated by Agr system. It was found that deletion of the ManNAc kinase encoding gene nanK decreased persister formation. Taken together, these results shed new light on the PSM dependent regulatory role of Agr system in persister formation and may have implications for clinical treatment of MRSA persistent infections.